Profiling of Physical Activity Usage In Selected Urban Green Spaces In Marikina City - Ty, Trizsa Jasmin C; Dimarucut, Alberto L; Castro, Camille B; Uy, Danielle Naomi L (UI Scholars Hub, 2025)
Urban Green Spaces (UGS) play an important role in providing opportunities for physical activity in urbanized cities. This observational cross-sectional study aims to profile two selected UGS, namely Marikina River Park and Marikina Heights Park Complex, in Marikina City, in the context of their use for physical activity and recreation. Interviews with two government officials were conducted to collect data on the historical background of the selected parks. Systematic observation, using the System for Observation of Play and Recreation in Communities tool, was conducted to observe park visitors and their physical activity for four days in each park. Each park’s target area's characteristics were identified and assessed before the observation period. Findings from the interviews indicate that the selected UGS were established for community and personal development. Each park contained areas suited for general use, rest, and socialization or for specific activities. Observations indicate that most visitors use the UGS for physical activity. A total of 47.91% engaged in moderate activity, 3.74% in vigorous activity, and 48.34% were observed to be sedentary. Various types of activity were recorded, with walking, biking, and dancing being the most common. Walking and biking visitors often used the park as part of their daily route. The majority of park visitors were male (52.55%), while females accounted for 47.45%. Teenagers made up the largest observed age group (49.83%), followed by adults (33.26%), children (13.62%), and older adults (3.30%). These findings indicate that the selected UGS serve their intended purpose, with most visitors engaging in physical activity. Nevertheless, further improvements aimed at specific activities may help attract demographic groups that were less represented. The physical design of the parks and the presence of structured programs could help increase participation among these groups. A built environment and organized activity can be used to encourage physical activity for specific demographics of park visitors.